Resistance mechanisms and drug susceptibility testing of nontuberculous mycobacteria - van Ingen, Jakko; Boeree, Martin J.; van Soolingen, Dick; Mouton, Johan W. (Drug resistance updates, 2012)
Nontuberculous mycobacteria (NTM) are increasingly recognized as causative agents of opportunistic infections in humans. For most NTM infections the therapy of choice is drug treatment, but treatment regimens differ by species, in particular between slow (e.g. Mycobacterium avium complex, Mycobacterium kansasii) and rapid growers (e.g. Mycobacterium abscessus, Mycobacterium fortuitum). In general, drug treatment is long, costly, and often associated with drug-related toxicities; outcome of drug treatment is poor and is likely related to the high levels of natural antibiotic resistance in NTM. The role of drug susceptibility testing (DST) in the choice of agents for antimicrobial treatment of NTM disease, mainly that by slow growers, remains subject of debate. There are important discrepancies between drug susceptibility measured in vitro and the activity of the drug observed in vivo. In part, these discrepancies derive from laboratory technical issues. There is still no consensus on a standardized method. With the increasing clinical importance of NTM disease, DST of NTM is again in the spotlight. This review provides a comprehensive overview of the mechanisms of drug resistance in NTM, phenotypic methods for testing susceptibility in past and current use for DST of NTM, as well as molecular approaches to assess drug resistance.